The power of social media as a labour campaigning tool: lessons from OUR Walmart and the Fight for 15 - Pasquier, Vincent; Wood, Alex (Brussels, 2018)
"This policy brief discusses how social media can help renew trade union collective action and strengthen the labour movement’s capacity to mobilise. It demonstrates how social media can strengthen campaigning activities by examining two recent union-led campaigns in the United States: ‘OUR Walmart’ and ‘Fight for 15’. Both campaigns made intensive use of social media and gained unexpected and significant victories on minimum wage increases and improvements to working conditions. However, while the potential benefits of social media for union campaigns are significant, a number of conditions need to be in place to be successful, and the brief also provides warnings about the limitations and potential risks of these new technologies."